Impact of the Environmental, Social, and Governance reporting framework on practices in JSE listed companies - Manyike, Nyanisi Nyeleti (University of the Witwatersrand, Johannesburg, 2023)
A company's long-term sustainability and financial performance are the most important goals all CEOs and managers aim to achieve. One way of achieving these objectives is by integrating ESG into a company’s investment decision-making processes. ESG reporting ensures that an organization is accountable for Environmental, Social, and Governance issues. The proposition that the author makes is that integrating ESG in investment decision-making processes will result in a company’s long-term sustainability together with improved financial performance. The study sampled 42 out of 100 respondents from an Asset Manager. The results show that, although some respondents do not fully agree that ESG integration in investment decision-making processes improves its financial performance, the majority hold the view that it achieves this goal and most particularly long-term sustainability of a company. As such, the findings from the 42 respondents confirm the two propositions made by the author. Although there is high agreement that ESG integration accomplishes the two said objectives, there are respondents who do not agree with the same. This study did not probe reasons for varying views, as such it is recommended that a mixed methods study be conducted in the future to understand in-depth reasons behind the responses
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Financial performance; CEOs; ESG; Investment; Environmental, Social, and Governance; JSE listed companies; UCTD; SDG-8: Decent work and economic growth